Widespread cortical functional disconnection in gliomas: an individual network mapping approach. Issue 2 (8th April 2022) - Silvestri, Erica; Moretto, Manuela; Facchini, Silvia; Castellaro, Marco; Anglani, Mariagiulia; Monai, Elena; D'Avella, Domenico; Della Puppa, Alessandro; Cecchin, Diego; Bertoldo, Alessandra; Corbetta, Maurizio
Abstract: Assessment of impaired/preserved cortical regions in brain tumours is typically performed via intraoperative direct brain stimulation of eloquent areas or task-based functional MRI. One main limitation is that they overlook distal brain regions or networks that could be functionally impaired by the tumour. This study aims (i) to investigate the impact of brain tumours on the cortical synchronization of brain networks measured with resting-state functional magnetic resonance imaging (resting-state networks) both near the lesion and remotely and (ii) to test whether potential changes in resting-state networks correlate with cognitive status. The sample included 24 glioma patients (mean age: 58.1 ± 16.4 years) with different pathological staging. We developed a new method for single subject localization of resting-state networks abnormalities. First, we derived the spatial pattern of the main resting-state networks by means of the group-guided independent component analysis. This was informed by a high-resolution resting-state networks template derived from an independent sample of healthy controls. Second, we developed a spatial similarity index to measure differences in network topography and strength between healthy controls and individual brain tumour patients. Next, we investigated the spatial relationship between altered networks and tumour location. Finally, multivariate analyses related cognitive scores across multiple cognitive domains (attention, language, memory, decision making) with patterns of multi-network abnormality. We found that brain gliomas cause broad alterations of resting-state networks topography that occurred mainly in structurally normal regions outside the tumour and oedema region. Cortical regions near the tumour often showed normal synchronization. Finally, multi-network abnormalities predicted attention deficits. Overall, we present a novel method for the functional localization of resting-state networks abnormalities in individual glioma patients. These abnormalities partially explain cognitive disabilities and shall be carefully navigated during surgery. Abstract : Silvestri et al . developed a new method to investigate resting-state brain networks in patients with gliomas. They showed that gliomas cause broad alterations of network topography occurring mainly in structurally normal regions outside the lesion. These abnormalities partially explain cognitive disabilities and shall be carefully navigated during surgery. Graphical Abstract: Graphical Abstract